Gene Therapy for Cystic Fibrosis: Overcoming Current Limitations and Future Directions - Wassan, Nadir Ali; Qammar, Asfia; Burki, Shahid; Arshad, Anam; Gul, Hassam; Mujtaba, Muhammad (Indus Journal of Bioscience Research, 2025)
Cystic fibrosis (CF) is a lethal inherited disorder resulting from mutations in the CFTR gene that cause improper chloride ion movement and clogging of the lungs with mucus. While classic therapies have been augmented by CFTR modulators and airway clearance techniques, these remain limited by expense, specificity for the mutation, and the need for lifetime therapy. Gene therapy has been suggested as a curative treatment, wherein the goal is to repair the defective CFTR gene through techniques such as CRISPR-Cas9, viral/non-viral vectors, and stem cell-based therapy. This study employed a mixed-methods setting, integrating survey-based assessment with a meta-analysis of existing literature to evaluate awareness, perception, and barriers to implementation of gene therapy among CF patients and caregivers in Punjab, Pakistan. A questionnaire was given to 65 participants, and qualitative data analysis with SPSS established a significant awareness gap, where socioeconomic status and education level were major determinants. Chi-square and ANOVA tests established statistically significant relationships between demographic variables and gene therapy acceptance. Moreover, the meta-analysis found consistent trends in current research indicating similar problems of limited accessibility, ethical concerns, and the necessity for improved gene delivery systems. The results reaffirm the necessity for further patient education, increased affordability, and more clinical verification to make gene therapy a therapeutic reality. In general, the research underscores the promise of gene therapy in CF while encouraging the implementation of multidisciplinary methods to overcome existing limitations. This study examines awareness and perceptions of gene therapy for cystic fibrosis in Punjab, Pakistan, revealing low knowledge levels influenced by socioeconomic factors. Challenges include cost, accessibility, safety concerns, and ethical implications. Future efforts must integrate research, policy reforms, and patient advocacy to enhance gene therapy’s feasibility and availability.